Terrorism and internet censorship. (November 2020) - Meserve, Stephen A; Pemstein, Daniel
The internet provides a powerful tool to terror organizations, enhancing their public messaging, recruitment ability, and internal communication. In turn, governments have increasingly moved to disrupt terror organizations' internet communications, and even democracies now routinely work to censor terrorist propaganda, and related political messaging, in the name of national security. We argue that democratic states respond to terror attacks by increasing internet censorship and broadening their capacity to limit the digital dissemination of information. This article builds on previous work suggesting this relationship, substantially improving measurement and estimation strategy. We use latent variable modeling techniques to create a new measure of internet censorship, cross nationally and over time, from internet firm transparency reports, and compare this measure to an expert-survey based indicator. Leveraging both measures, we use a variety of panel specifications to establish that, in democracies, increases in terror predict surges in digital censorship. Finally, we examine the posited relationship using synthetic control methods in a liberal democracy that experienced a large shock in terror deaths, France, showing that digital censorship ramped up after several large terrorist attacks.